2002
DOI: 10.1136/heart.87.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of idiopathic cardiomyopathy in Japan: results from a nationwide survey

Abstract: Objective: To estimate the total number of patients with idiopathic cardiomyopathy in Japan and the prevalence of the disorder. Design: A nationwide epidemiological survey. Setting: Hospitals selected randomly from among all hospitals in Japan. Patients: Patients presenting with any of the three types of idiopathic cardiomyopathy: dilated cardiomyopathy, hypertrophic cardiomyopathy, and restrictive cardiomyopathy. Main outcome measures: The total number of patients in Japan was estimated using the sampling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 19 publications
5
63
1
Order By: Relevance
“…Our regional cohort in the Kochi RYOMA study was older than HCM cohorts in previous studies, [7][8][9][10][11]18 probably because Kochi Prefecture, where our study was performed, is located far from urban areas and is one of the most aged communities in Japan. The percentage of male patients in our cohort (64%) was similar to the percentages in previous studies in Western countries and Japan.…”
Section: Hcm Populationmentioning
confidence: 93%
“…Our regional cohort in the Kochi RYOMA study was older than HCM cohorts in previous studies, [7][8][9][10][11]18 probably because Kochi Prefecture, where our study was performed, is located far from urban areas and is one of the most aged communities in Japan. The percentage of male patients in our cohort (64%) was similar to the percentages in previous studies in Western countries and Japan.…”
Section: Hcm Populationmentioning
confidence: 93%
“…Indeed FHC is the most common cause of sudden cardiac death in young athletes [21]. The prevalence of FHC is believed to be about 0.2%, or 1 in 500 [22,23]. However despite its relatively high prevalence, the mortality rate for FHC-related deaths in an unselected population was estimated to be only 1% [24].…”
Section: Familial Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…The Our study showed an increased preponderance of the condition among the males (78.7%) when compared to females (21.3%), with the sex ratio being 3.7:1, which indicates a higher male preponderance compared to previous studies from western (2.9:1) and Japanese (2.3:1) populations. [11,12] The sex ratio in the different subsets of HCM were found to be 3. In general 31% of the HCM probands have a familial history of the disease, which is in conformation with other reports.…”
Section: Resultsmentioning
confidence: 99%